logo for solving-math-problems.com
leftimage for solving-math-problems.com

simplify -7y -(2y - 9) - algebra

by Misty
(Washigton)










































how do you simplify:

-7y -(2y - 9)

show all work?

Use PEMDAS

P = Parentheses, Complete 1st

E = Exponents, Complete 2nd

M = Multiplication, Complete 3rd

D = Division, Complete 4th

A = Addition, Complete 5th

S = Subtraction, Complete 6th

Comments for simplify -7y -(2y - 9) - algebra

Click here to add your own comments

Mar 08, 2012
Simplify Expression
by: Staff


Question:

by Misty
(Washington)


how do you simplify -7y -(2y - 9) show all work?



Answer:

-7y -(2y - 9)


You can evaluate this expression using the PEMDAS order of operations.

PEMDAS is an acronym. PEMDAS is an abbreviation for a six step process. The order of the letters tells you which mathematical operation to complete first, second, . . . etc.


P = Parentheses, Complete 1st

E = Exponents, Complete 2nd

M = Multiplication, Complete 3rd

D = Division, Complete 4th

A = Addition, Complete 5th

S = Subtraction, Complete 6th




Step 1: you should evaluate the expression inside each set of PARENTHESES

PEMDAS order of evaluation: PARENTHESES, exponents, multiplication, division, addition, and subtraction

There is only one set of parentheses.

(2y - 9)


Since the value of the variable “y” is not known, the value of the expression inside the parentheses remains unchanged.


Your original expression has not changed:

-7y -(2y - 9)



Step 2: evaluate EXPONENTS


PEMDAS order of evaluation for (simplified) overall expression: parentheses, EXPONENTS, multiplication, division, addition, subtraction

There are no exponents to evaluate.


Step 3: MULTIPLICATION


PEMDAS order of evaluation: parentheses, exponents, MULTIPLICATION, division, addition, subtraction

There is one multiplication process which should be completed:

-(2y - 9)

Using the distributive law:

= (-1) * (2y - 9)

= (-1) * (2y) + (-1) * (-9)

= -2y + 9

A recap of the PEMDAS simplification process up to this point is shown below:

-7y -(2y - 9)

= -7y + (-1) * (2y - 9)

= -7y + (-1) * (2y) + (-1) * (-9)

= -7y - 2y + 9


Step 4: DIVISION


PEMDAS order of evaluation: parentheses, exponents, multiplication, DIVISION, addition, subtraction

There are no division operations to evaluate.

Step 5: evaluate ADDITION & SUBTRACTION

PEMDAS order of evaluation: parentheses, exponents, multiplication, division, ADDITION, SUBTRACTION

= -7y - 2y + 9

= (-7y - 2y) + 9

= -9y + 9


After completing the last step, you are finished.


The final answer to your question is: -9y + 9



A step-by-step recap of the entire process is shown below:

-7y - (2y - 9)


= -7y + (-1) * (2y - 9)

= -7y + (-1) * (2y) + (-1) * (-9)

= -7y - 2y + 9

= (-7y - 2y) + 9

= -9y + 9



Thanks for writing.

Staff
www.solving-math-problems.com



Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com